KAJIAN ATAS FUNGSI SOSIAL PADA TINDAKAN EKONOMI PELAKU LEMBAGA KEUANGAN MIKRO SYARIAH - Satria, Awang Tri; Burhan, Umar; Manzilati, Asfi (Trunojoyo University of Madura, 2015)
This study aims to: 1) determine how actors in sharia microfinance institutions provide the perception toward the social function of the economic action undertaken. 2) determine the form of the social functions performed by the actors in sharia microfinance institutions. This study used a qualitative method with phenomenological approach.The findings of this study are: 1) the perception of the social function by the actors of sharia microfinance institutions respectively: a) perception of social function is as management of zakat, infaq, and alms known in the concept of Baitul Maal. b) the social function as a medium of empowerment of poor communities where the sharia microfinance institutions are capable in producing new entrepreneurs. c) the social function as propaganda/symbols of Islam, Islamic microfinance institutions serve to eradicate the practice of existing usurer in the community. 2) The form of social functions held by sharia microfinance institutions are: a) The distribution of social grants, the distribution of development aid in the form of mosques, procurement assistance of Al-Quran,Â home renovation, distribution of Zakat funds as well as scholarships to students who cannot afford school. b) Help the poor public capital, capital assistance is intended for the poor, capital assistance is also easy for small traders in accessing financing. c) Optimalization the role of sharia microfinance institutions by opening branches in remote areas which aim to facilitate the public in accessing Sharia financial institutions and also propaganda symbols of Islam in religious activities.